CUSTOMER DELIGHT DAN LOYALITAS PELANGGAN (Fokus Ekonomi, 2008)
Customer satisfaction is a minimal requirement in a modern marketing concept. Managers who have the quality commitment will always no only satisfaction and also create customer delight. Customers who really obtain the delight will be loyal to specific brand. Loyalty is the indicator of customer performance which is always loyal to deal with the specific company. Thus the company can exist if it can give customer delight and win the competition in globalization era. Key Words: Customer Satisfaction, Customer Delight and Loyalty